Legend of the Sentinels: Development of Lung Resident Memory T Cells and Their Roles in Diseases - Qian, Youkun; Zhu, Yicheng; Li, Yangyang; Li, Bin (Frontiers in Immunology, 2021)
SARS-CoV-2 is wreaking havoc around the world. To get the world back on track, hundreds of vaccines are under development. A deeper understanding of how the immune system responds to SARS-CoV-2 re-infection will certainly help. Studies have highlighted various aspects of T cell response in resolving acute infection and preventing re-infections. Lung resident memory T (TRM) cells are sentinels in the secondary immune response. They are mostly differentiated from effector T cells, construct specific niches and stay permanently in lung tissues. If the infection recurs, locally activated lung TRM cells can elicit rapid immune response against invading pathogens. In addition, they can significantly limit tumor growth or lead to pathologic immune responses. Vaccines targeting TRM cells are under development, with the hope to induce stable and highly reactive lung TRM cells through mucosal administration or "prime-and-pull" strategy. In this review, we will summarize recent advances in lung TRM cell generation and maintenance, explore their roles in different diseases and discuss how these cells may guide the development of future vaccines targeting infectious disease, cancer, and pathologic immune response.